Therapeutic targeting of microglia mediated oxidative stress after neurotrauma - Smith, Austin N.; Shaughness, Michael; Collier, Sean; Hopkins, Deanna; Byrnes, Kimberly R. (Frontiers in Medicine, 2022)
Inflammation is a primary component of the central nervous system injury response. Traumatic brain and spinal cord injury are characterized by a pronounced microglial response to damage, including alterations in microglial morphology and increased production of reactive oxygen species (ROS). The acute activity of microglia may be beneficial to recovery, but continued inflammation and ROS production is deleterious to the health and function of other cells. Microglial NADPH oxidase (NOX), mitochondria, and changes in iron levels are three of the most common sources of ROS. All three play a significant role in post-traumatic brain and spinal cord injury ROS production and the resultant oxidative stress. This review will evaluate the current state of therapeutics used to target these avenues of microglial-mediated oxidative stress after injury and suggest avenues for future research.